Unintended Consequences : Spillovers from Nigeria's Fuel Pricing Policies to Its Neighbor - Mlachila, Montfort (IMF Working Papers; Working Paper ;, 2016)
This paper examines the constraints that negative externalities (i.e., smuggling from a large neighbor) impose on the application of automatic fuel price adjustment mechanisms. It is often recommended to establish an automatic price adjustment mechanism to reduce fuel subsidy expenditures, but this approach may not work in the presence of these externalities. The paper illustrates the constraints by examining the case of Nigeria, a major oil exporter that subsidizes gasoline, and that of Togo, an oil importer and neighbor of Nigeria. It finds that the price differential between formal prices in Togo and Nigeria is the main driver of changes in formal sector gasoline consumption. Specifically, the lower the formal price in Nigeria, the higher is smuggling from Nigeria to Togo, and the lower the tax base in Togo. The econometric results suggest that, unless the real economy is performing very well, increases in pump prices in Togo are likely to erode the tax base, unless there are greater border controls. The unintended consequences of Nigeria's pricing policies are the constraint they impose on fuel pricing policies of its neighbors and the subsidy Nigeria transfers to them (equivalent to at least 3 percent of Togo's GDP in 2011), three-quarters of which was captured by smugglers in 2011, while one-quarter enhanced consumers surplus through lower gasoline prices.